2017
DOI: 10.1016/j.maturitas.2017.07.008
|View full text |Cite
|
Sign up to set email alerts
|

Menopause in Latin America: Symptoms, attitudes, treatments and future directions in Costa Rica

Abstract: Similar to their US counterparts, Costa Rican women enter menopause at ~50 years of age, have similar symptoms, including hot flashes and night sweats, as well as an overall negative attitude toward the menopausal transition. One study of rural women in Monteverde reported that women knew little about the menopausal transition, as the subject was not discussed. Similar to other Latin American women, the use of hormone therapy by Costa Rican women is low and instead they use alternative therapies, including mas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 32 publications
0
5
0
Order By: Relevance
“…In addition, menopause may also cause bone loss, breast diseases, problems in cardiovascular system, mood and cognitive dysfunctions, sexual issues, etc. [ 3 , 4 ]. The risk of ovarian cancer is also elevated during perimenopause [ 5 ].…”
Section: Introductionmentioning
confidence: 99%
“…In addition, menopause may also cause bone loss, breast diseases, problems in cardiovascular system, mood and cognitive dysfunctions, sexual issues, etc. [ 3 , 4 ]. The risk of ovarian cancer is also elevated during perimenopause [ 5 ].…”
Section: Introductionmentioning
confidence: 99%
“… 2007 , 2009 ; Locklear et al. 2007 , 2010 , 2017 ). Results of this work demonstrated that extracts of P. dioica not only bound to the oestrogen receptors, but also induced the transcription of oestrogen responsive genes in MCF-7 cells (Doyle et al.…”
Section: Discussionmentioning
confidence: 98%
“…As part of our work in Central America, we have identified more than 17 plant species used in Costa Rica to treat women’s reproductive health disorders with a focus on menopause (Locklear et al. 2007 , 2017 ; Doyle et al. 2009 ).…”
Section: Introductionmentioning
confidence: 99%
“…In addition, differences in attitudes towards menopause transition and symptoms have also been observed among Latin American and Asian women from different ethnic groups. [27][28][29][30][31] Many women used online resources to find information on perimenopause, although many were dissatisfied with the available information. The healthcare needs of women experiencing menopause transition include easy access to data and sharing experiences with healthcare providers without a rigid and patronizing assessment of attitudes and behaviors.…”
Section: Discussionmentioning
confidence: 99%